Impact of pharmacist interventions on immunisation uptake: a systematic review and meta-analysis - Mohamad Hafiz Abd Rahim; Siti Hajar Mahamad Dom; Mohd Shah Rezan Hamzah; Siti Hawa Azman; Zahirah Zaharuddin; Mathumalar Loganathan Fahrni (Taylor & Francis Group, 2024)
Background Under-utilisation of immunisation services remains a public health challenge. Pharmacists act as facilitators and increasingly as immunisers, yet relatively little robust evidence exists of the impact elicited on patient health outcome and vaccination uptake. Objective To evaluate the influence of pharmacist interventions on public vaccination rate. Methods SCOPUS, PubMed, and Web of Science were searched from inception to April 2023 to retrieve non- and randomised controlled clinical trials (RCTs). Studies were excluded if no comparator group to pharmacist involvement was reported. Data extraction, risk of bias assessments, and meta-analyses using random-effect models, were performed. Results Four RCTs and 15 non-RCTs, encompassing influenza, pneumococcal, herpes zoster, and tetanus-diphtheria and pertussis vaccine types, and administered in diverse settings including community pharmacies, were included. Pooled effect sizes revealed that, as compared to usual care, pharmacists, regardless of their intervention, improved the overall immunisation uptake by up to 51% [RR 1.51 (1.28, 1.77)] while immunisation frequency doubled when pharmacists acted specifically as advocators [RR 2.09 (1.42, 3.07)]. Conclusion While the evidence for pharmacist immunisers was mixed, their contribution to immunisation programmes boosted public vaccination rate. Pharmacists demonstrated leadership and acquired indispensable advocator roles in the community and hospital settings. Future research could explore the depth of engagement and hence the extent of influence on immunisation uptake.